Proton-Enhanced (13)C Nuclear Magnetic Resonance of Lipids and Biomembranes - Urbina, Julio (1974)
A recently developed nuclear double resonance technique which permits sensitive detection, together with high resolution, of rare spins in solids or other dipolar-coupled nuclear systems [Pines, Gibby, and Waugh (1973) J. Chem. Phys. 59, 569] has been applied to the study of natural abundance (13)C-nuclear magnetic resonance in lipid mesophases and of selectively labeled carbon sites in bacterial membranes. Detailed microscopic information on the molecular organization and phase transitions of the lipid phases and their interaction with ions and other molecules can be obtained from the study of the chemical shift anisotropies and dynamical aspects of the (13)C NMR spectra of unsonicated lipid dispersions (liposomes). Experiments are reported which demonstrated the feasibility of quantitatively observing the (13)C-nuclear magnetic resonance of specifically labeled sites in unperturbed Escherichia coli membrane vesicles for the study of the physical state of the lipids with the aim of relating it to the known lipid-dependent functional properties of the membranes.